A passive and active microwave-vector radiative transfer (PAM-VRT) model. (November 2015) - Yang, Jun; Min, Qilong
Abstract: A passive and active microwave vector radiative transfer (PAM-VRT) package has been developed. This fast and accurate forward microwave model, with flexible and versatile input and output components, self-consistently and realistically simulates measurements/radiation of passive and active microwave sensors. The core PAM-VRT, microwave radiative transfer model, consists of five modules: gas absorption (two line-by-line databases and four fast models); hydrometeor property of water droplets and ice (spherical and nonspherical) particles; surface emissivity (from Community Radiative Transfer Model (CRTM)); vector radiative transfer of successive order of scattering (VSOS); and passive and active microwave simulation. The PAM-VRT package has been validated against other existing models, demonstrating good accuracy. The PAM-VRT not only can be used to simulate or assimilate measurements of existing microwave sensors, but also can be used to simulate observation results at some new microwave sensors. Highlights: A novel microwave vector radiative transfer model is developed. It can simulate passive and active microwave radiative transfer simultaneously. It can be applied to simulate measurements for different types of viewing geometry. The accuracy of this model has been validated against other existing models.